Luwian identities : culture, language and religion between Anatolia and the Aegean. - Mouton, Alice. (Culture and History of the Ancient Near East, 2013)
The Luwians inhabited Anatolia and Syria in late second through early first millennium BC. They are mainly known through their Indo-European language, preserved on cuneiform tablets and hieroglyphic stelae. However, where the Luwians lived or came from, how they coexisted with their Hittite and Greek neighbors, and the peculiarities of their religion and material culture, are all debatable matters. A conference convened in Reading in June 2011 in order to discuss the current state of the debate, summarize points of disagreement, and outline ways of addressing them in future research. The papers presented at this conference were collected in the present volume, whose goal is to bring into being a new interdisciplinary field, Luwian Studies. \'To conclude, the editors of this volume on Luwian identities and the authors of the individual papers are to be congratulatedwith a successful sequel to TheLuwians of 2003 edited by Melchert and with yet another substantial brick in the foundation of the incipient discipline of Luwian studies.\' Fred C. Woudhuizen